Removal of Toxic Cations from Aqueous Solutions using Ginger Root Waste - Jude Chinedu Onwuka; Stephen Azubuike Igberi; Timothy M. Akpomie (Pandawa Institute, 2022)
Recently, the harmful impact of toxic metals in the aquatic environment cannot be over emphasized again. This work investigated the potential application of ginger root waste (GRW) to remove toxic cations (Cd2+ and Pb2+) from the aqueous medium. Batch adsorption examination was carried out as a function of sorbent dose, initial metal ion concentration, contact time, and temperature. The sorption equilibrium of the metal ions onto the GRW was subjected to Langmuir, Freundlich, Elovich and Redlich-Peterson isotherm models over concentration ranges of 10-50 mg/L. Sorption information was used for kinetic and thermodynamic modeling. The GRW materials before and after sorption was characterized using FTIR and SEM. Results showed higher removal percentage of Cd2+ over Pb2+ ions in all the factors studied. The Redlich – Peterson isotherm model affirmed that sorption of Cd2+ and Pb2+ occurred in a heterogenous surface of the sorbent which is strongly influenced by multiple micropores and caves. Kinetic studies revealed that the sorption was controlled through intra-particle diffusion model aided by surface and chemical reactions. Meanwhile, thermodynamic parameters indicated that the Cd2+ and Pb2+ sorption process was endothermic, however, non-spontaneous at temperature of 303 and 313 K. The FTIR and SEM data showed the evidence of successful sorption of the toxic cations on to the sorbent material.